Alat Pencuci Kedelai untuk Mengurangi Kelelahan Kerja di Home Industry Tempe - Indah Rizkya Tarigan; Ukurta Tarigan; Dina Arwina Dalimunthe (Universitas Teuku Umar, 2023)
Tempe is a traditional Indonesian food made from fermented soybeans, which is in great demand by the public and highly nutritious. The soybean washing process in the tempe production process is an important process because it has an impact on the quality and cleanliness of the tempe produced. The washing process was carried out twice, namely before and after the boiling process. The soybean washing process in the home industry uses simple equipment that does not support normal work positions. As a result, workers get tired easily. If it lasts for a long time, it causes permanent work-related pain. This paper describes the process of procuring an ergonomic soybean washing machine so as to reduce work fatigue. In the short term, the benefits that are immediately felt by the Home Tempe Industry business partners are that the soybean washing process becomes lighter and less tiring as before. The proposed tool can also increase production capacity because it can reduce the washing process time and worker rest time. The capacity of one washing can accommodate 50-60 kg of soybeans so that the repetition of washing becomes less and results in a shorter production process time. In the end, the production capacity per day can be increased and the productivity of the Home Tempe Industry partners also increases.